THE EFFECTIVENESS OF LEARNING MATHEMATICS USING THE PREVIEW OF LEARNING STRATEGIES, QUESTIONS, READ, REFLECTION, RECITE, REVIEW (PQ4R) AND EXPOSURE TOWARD MATHEMATICS LEARNING OUTCOMES - Okta Wibowo; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Learning that teachers dominate, communication tends to one direction, and students' inactivity is why students often forget the material so that the learning results are not maximum. PQ4R was created to improve the memory of the matter. This research aims to determine the difference between the use of PQ4R learning strategies and learning strategies that have been used in place of research that is Expository, in its relation to the mathematics learning outcomes of students VIII grade even semester SMP Negeri 4 Sewon Bantul academic year 2016/2017. This study used a posttest-only control group design. The population in this study are three classes: the sample taken two classes with random sample technique. Data collection was conducted with the test method. The instrument used is a multiple-choice test. Before analyzing the data, a prerequisite test consisting of normality test and homogeneity test was performed. The research results on the significant level of 5% and df = 62 indicate that: (1) there is a difference in students' mathematics learning between using PQ4R learning strategies and using expository learning strategies. This is indicated by the value of  = 1.99897 and =  = 11.54804 which mean  > . Moreover, (2) PQ4R learning strategies are more effective than expository strategies. This is indicated by the value of = 1.6698 and = = 11,54804 which mean  > .